Long-term outcomes of resection for locoregional recurrence of colon cancer: A retrospective descriptive cohort study. Issue 9 (September 2021) - Chesney, Tyler R.; Metz, Jeffrey J.; Nadler, Ashlie; Quereshy, Fayez A.; Ashamalla, Shady; Acuna, Sergio A.; Swallow, Carol J.
Abstract: Introduction: Resection for isolated distant recurrence of colon cancer is well accepted. Resection for locoregionally recurrent colon cancer (LRCC) is not well studied. We evaluated the long-term outcomes of curative-intent resection for LRCC. Methods: All patients undergoing curative-intent resection for LRCC at three specialized cancer centers affiliated with the University of Toronto were identified (1993-2017). Follow-up included serial clinical assessment, colonoscopy, CEA, and cross-sectional imaging. Overall survival (OS), cancer-specific survival (CSS) and time to re-recurrence were estimated using Kaplan-Meier method and cumulative incidence function. The association between resection margins and outcome was assessed with Cox models. Results: 117 patients were included in the study cohort. Median follow-up was 53 months (IQR: 34-101). OS was 75% (95% CI: 68-84) at 5 years, and 69% (95% CI: 59-79) at 10 years. CSS was 78% (95% CI: 70-86) at 5 years and 72% (95% CI: 63-83) at 10 years. The rate of re-recurrence was 22% (95% CI: 14-31) at 5 years, and 27% (95% CI: 16-39) at 10 years. Negative resection margin (R0) was associated with improved OS (HR 3.33, 95% CI: 1.85–6.00, p < 0.01). There were no postoperative deaths; complications with Clavien-Dindo grade > II occurred in 12% of patients. Perioperative chemotherapy was used in 63% of patients and radiotherapy in 37%. Conclusion: In selected patients with LRCC, excellent OS, CSS and low re-recurrence rates were observed, and R0 resection predicted better outcomes. These findings support consideration of resection for LRCC in fit patients after review at a multidisciplinary cancer conference.